A Nck‐associated protein 1‐like protein affects drought sensitivity by its involvement in leaf epidermal development and stomatal closure in rice. (18th March 2019) - Huang, Lichao; Chen, Long; Wang, Lan; Yang, Yaolong; Rao, Yuchun; Ren, Deyong; Dai, Liping; Gao, Yihong; Zou, Weiwei; Lu, Xueli; Zhang, Guangheng; Zhu, Li; et al.
Summary: Water deficit is a major environmental threat affecting crop yields worldwide. In this study, a drought stress‐sensitive mutant drought sensitive 8 ( ds8 ) was identified in rice ( Oryza sativa L.). The DS8 gene was cloned using a map‐based approach. Further analysis revealed that DS8 encoded a Nck‐associated protein 1 (NAP1)‐like protein, a component of the SCAR/WAVE complex, which played a vital role in actin filament nucleation activity. The mutant exhibited changes in leaf cuticle development. Functional analysis revealed that the mutation of DS8 increased stomatal density and impaired stomatal closure activity. The distorted actin filaments in the mutant led to a defect in abscisic acid (ABA)‐mediated stomatal closure and increased ABA accumulation. All these resulted in excessive water loss in ds8 leaves. Notably, antisense transgenic lines also exhibited increased drought sensitivity, along with impaired stomatal closure and elevated ABA levels. These findings suggest that DS8 affects drought sensitivity by influencing actin filament activity. Significance Statement: DS8 encodes a NAP1‐like protein that affects drought sensitivity by its involvement in leaf epidermal development and stomatal closure in rice, revealing a molecular mechanism concerning the SCAR/WAVE‐Arp2/3 complex in the drought stress response.